Design of Jig for Coordinate Measuring Machine / Norasikin Hussin ...[et al.] - Hussin, Norasikin; Ibrahim, Dzullijah; Mohd Yahya, N. H.; Zulkkhiflee, Nor Izlan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This project is about the design of jig for Coordinate Measuring Machine (CMM) in metrology laboratory. The CMM is one of precision measuring devices for measuring the physical geometrical characteristics of the product. Measurements are defined by a measuring probe touch the surface of the product. Currently, the box and plasticine are needed as a vice because there is no special vise in CMM to hold, clamp and support the workpiece. The existing vice is not properly in the measurement process but its used for the workpiece with a thickness less than 40mm and measuring probe can touch the workpiece. Because of that, the objective of the design of jig for CMM is to improve the measurement process in order to replace the existing vice. In other words, the design of jig is to ensure the method of measuring process is the correct to obtain the accuracy of measurement. The function of this jig is to hold, support and clamp the workpiece. The conceptual design is used to choose the best design. Based on the feedback obtained from the survey and benchmark, three designs of the jig; design A, B, and C have been evaluated using conceptual selection. The design C is selected as new design since the evaluation result in screening method gave the highest net score. The new design of jig is drawn and analyzed using SolidWorks software. Aluminium and ABS plastics were selected as selection material for the jig. The fabrication of jig has been done with a conventional milling machine and 3D printing. As a result, the jig is suitable and acceptable to apply in engineering measurement because of the accuracy is ±0.01mm.